Efek Aplikasi Smartphone (Promotif Dan Preventif) Terhadap Perubahan Gaya Hidup Pada Prediabetes: Literature Review - Dini Pudjiandarini Soekardjan; FX. Widiantoro; Elizabeth Ari Setyarini (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Prediabetes is high risk developing type 2 diabetes mellitus (T2DM). Modification in lifestyle plays an important role to avoid the prognosis of T2DM and its complications in the future. The aim of this literature is to identify the effect of smartphone app (promotive and preventive) to lifestyle change in prediabetes. Searching strategy used PICO approach by keywords in the on PubMed (1.581) and Cochrane Library (699) databased. The Critical Appraisal is used to evaluate the articles. Twelve articles have been in this literature with intervention: voice mail (1), phone call (1), text messages (3), web-based (3), applications (4). Two articles showed significant to increase motivation and education (promotion). Six articles were reported significantly increasing physical activity and weight loss (prevention). One article (promotive and preventive) reported significantly to promote knowledge and physical activity. Three articles demonstrated not significant to modify lifestyle of prevent T2DM (2 articles of prevention, 1 article of promotion and prevention, respectively). Recent review suggest that the smartphone app can help to slow-down the progression of diseases in individual with prediabetes and as a reference to construct effective program to reduce the morbidity and mortality associated with T2D.